Using Disaggregated Poverty Maps to Plan Sectoral Investments - Hentschel, Jesko (World Bank, Washington, DC, 2012)
This poverty note analyzes the usefulness of poverty maps, and how they can be constructed using census and survey data, for the use and benefit of policy makers to focus scarce development resources. The note goes on to describe various kinds of poverty maps, such as those based on indexes of welfare, basic needs indicators, and disaggregated consumption-based factors. Methodologies to create these maps, are further discussed at some length.